2009
DOI: 10.1073/pnas.0802864106
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and mitochondrial fatty acid β-oxidation link obesity to early tumor promotion

Abstract: Obesity is associated with increased risk for developing pancreatic cancer, and it is suggested that insulin resistance provides the missing link. Here we demonstrate that under the context of genetic susceptibility, a high fat diet (HFD) predisposes mice with oncogenic K-ras activation to accelerated pancreatic intraepithelial neoplasm (PanIN) development. Tumor promotion is closely associated with increased inflammation and abrogation of TNFR1 signaling significantly blocks this process underlining a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 31 publications
(33 reference statements)
7
134
0
2
Order By: Relevance
“…A recent study revealed that high-fat-diet-induced obesity in mice accelerated the development of PanIN in the context of embryonic KRas activation through changes in energy metabolism. These data suggested changes in energy metabolism rather than insulin resistance as key elements in early carcinogenesis of PDAC (Khasawneh et al, 2009). Recent evidence has also established a link between low serum levels of ZAG and obesity in humans; however, whether ZAG serum levels are also related to insulin resistance is still under debate (Marrades et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that high-fat-diet-induced obesity in mice accelerated the development of PanIN in the context of embryonic KRas activation through changes in energy metabolism. These data suggested changes in energy metabolism rather than insulin resistance as key elements in early carcinogenesis of PDAC (Khasawneh et al, 2009). Recent evidence has also established a link between low serum levels of ZAG and obesity in humans; however, whether ZAG serum levels are also related to insulin resistance is still under debate (Marrades et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that tobacco smoke acts as tumor promoter via triggering chronic inflammation . Similarly, obesity promotes tumorigenesis in the liver and pancreas partially through obesity-induced chronic inflammation (Khasawneh et al, 2009, Park et al, 2010. However, not all of chronic inflammatory diseases increase cancer risk.…”
Section: Interplays Between Inflammation and Tumorigenesismentioning
confidence: 99%
“…LSL-kRrasG12D mice were crossed to p48-Cre animals to generate mice with pancreas-specific (p48-kRas) and activate oncogenic kRas (Khasawneh et al, 2009). The KCMF1-deficient embryonic stem cell line (XE-080) was obtained from Bay Area Functional Genomics Consortium (BayGenomics, Berkeley, CA, USA), injected into 129SV/NMRI male chimeras and mated to C57BL/6J females following standard procedures.…”
Section: Animalsmentioning
confidence: 99%